Box fermentation and solar drying improve the nutrient composition and organoleptic quality of chocolate from cocoa beans - Obinze, Sandra; Ojimelukwe, Philippa C.; Eke, Ben A. (Frontiers in Sustainable Food Systems, 2022)
Chocolate is a well liked and popular food product made from the cocoa bean. The objective of this research was to evaluate the effects of fermentation and drying (key processes) of the cocoa bean on chocolate quality. Fermentation was carried out in a wooden box for 168h with periodic turning after every 48h. The succession of microorganisms during fermentation was monitored. Both the fermented and unfermented samples were solar dried. Their nutrient and phytochemical contents were evaluated. Sensory properties of chocolate, produced from the two samples were compared. The initial temperature of the fermenting cocoa mash was 30oC. It rose to 46oC by the 96th hour of fermentation and sharply declined by the 120th hour. Candida, Pseudomonas and Staphylococcus spp were probable organisms identified with the fermenting mass at the initial stage of the fermentation. Lactic acid bacteria dominated after 72h. Bacillus spp was also observed until the 168th hour. Solar drying of unfermented bean lasted for 4 days, while that of fermented bean lasted for 3 days. Fermentation increased the protein, ash and carbohydrate contents of the cocoa beans. It also improved the sensory attributes of chocolate from the cocoa beans.